2009
DOI: 10.12968/bjcn.2009.14.2.38760
|View full text |Cite
|
Sign up to set email alerts
|

Chronic heart failure: promoting quality of life

Abstract: There are growing numbers of people with heart failure, which is disabling for the individuals and costly for the health services. Heart failure is often associated with anxiety and depression. Nurses can improve patients' well-being by promoting regular exercise and self-care. Palliative care, which includes specialist heart failure services improves end-of-life experiences. This article reports the findings of a literature review derived from a search of 5 electronic databases to identify studies relating to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
3
7
0
3
Order By: Relevance
“…This finding supports previous findings, which also revealed a low level of self-care in HF patients. 12,13 Notably, the mean score for self-confidence was 39.7, which is much lower than the score of 85.8 obtained by Tung and colleagues 14 from another study in Taiwan. This might be due to participants being recruited from a rural area in Taiwan, while the previous study recruited participants from an urban area in Taipei, Taiwan.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding supports previous findings, which also revealed a low level of self-care in HF patients. 12,13 Notably, the mean score for self-confidence was 39.7, which is much lower than the score of 85.8 obtained by Tung and colleagues 14 from another study in Taiwan. This might be due to participants being recruited from a rural area in Taiwan, while the previous study recruited participants from an urban area in Taipei, Taiwan.…”
Section: Discussionsupporting
confidence: 90%
“…Relative to these findings, previous research demonstrated that self-care among HF patients is considered low. 12,13 In Taiwan, Tung and colleagues 14 found a low level of self-care maintenance and management, although self-care confidence was adequate.…”
mentioning
confidence: 99%
“…This loss of functions is associated with physical symptoms and the adverse effects of drugs, to comorbidities, loss of cognitive and role functions. Some studies suggest there is a strong association between physical dimension of the HRQOL and depression (7,24) . The results of the present study were similar to those found by other investigations, whose individuals presented higher scores in the physical dimension compared to the emotional one (7,12) .…”
Section: Discussionmentioning
confidence: 99%
“…All healthcare providers strive to improve the HRQoL of the people they serve. Improving HRQoL is particularly salient for nurses, given their holistic approach to providing patient care (Hacker 2009), because nurses can improve patients’ well‐being by promoting regular exercise and self‐care (While & Kiek 2009). Our study has revealed that quality‐of‐life physical component mean scores were higher for moderately active patients.…”
Section: Discussionmentioning
confidence: 99%